CHARACTERISTICS AND FORMS OF COMPETITIVENESS OF FINANCIALLY INDEPENDENT STATE ENTITIES - Adizov, Bobir Bakhtiyorovich (THE INNOVATION ECONOMY, 2026)
This article is devoted to elucidating the economic essence, specific characteristics, and manifestations of the competitiveness of financially independent state higher education institutions (HEIs). Different scientific approaches (economic, rating and indicator-based, institutional, innovation-research) related to the study of the competitiveness of HEIs are systematized and compared. Furthermore, based on existing approaches, an author's definition has been developed, and a comparative analysis of the competitiveness of HEIs and manufacturing enterprises is presented. As a result of the research, the "Mutnis" (absolute and relative competitiveness) hybrid model of competitiveness for financially independent HEIs is proposed.